Italy : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Italy. (IMF Staff Country Reports; Country Report, 2019)
This 2018 Article IV Consultation highlights that Italy has been struggling with low economic growth and poor social outcomes and structural weaknesses have been at the core of this economic underperformance. Growth is projected to slow further, and the risk of recession has risen. The extent to which risks materialize depends largely on Italy's policies. The authorities felt strongly that a fiscal stimulus is needed to promote economic growth and improve social outcomes. The authorities are also seeking to reduce temporary employment and support job search. The report suggests that faster potential growth is the only durable way for Italy to improve outcomes and enhance resilience. A package of structural reforms, a credible fiscal consolidation based on growth-friendly and inclusive measures, and bank balance sheet strengthening structural reforms, fiscal policy, and financial stability are also recommended. As by facilitating re-alignment of wages with productivity at the firm and regional levels, Italy's high structural unemployment would fall, as would the continued heavy resort to temporary employment.